Gerakan Manajemen Literasi dalam Meningkatkan Minat Baca Siswa Sebagai Transfigurasi Perpustakaan di MAS YPK Cijulang - Usep Purkon Ramdani; Gita Puspita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This research aims to describe and identify the planning and implementation of the School Literacy Movement (GLS) program as well as the obstacles and supporters in implementing the program. The school literacy movement is a comprehensive and sustainable effort to foster students' interest in reading and make schools a learning organization whose citizens are literate throughout life and of course become one of the transformations of libraries in schools. This research uses a qualitative approach. The location of this research is MA YPK Cijulang with the research subjects being the school principal, students and class teachers. Data was collected through observation, interviews with school principals and class teachers. In implementing the school literacy movement, school principals have a very big role considering that government policy allows each school institution to develop programs that have been agreed to by the government. The results of this research indicate that the implementation of the literacy movement program at MA YPK Cijulang can increase students' reading interest and reading ability. The product of the Literacy Movement program at MA YPK Cijulang is the activity of reading a book for 15 minutes and reading 3 surahs in chapter 30 for 15 minutes every morning.